City-Level Action in a City-Wide Urban Commons. Amsterdam, 1977-1983 - Hans Pruijt (Coordinamento SIBA, 2020)
In the late 1970s, Amsterdam's squatted domain grew to comprise hundreds of buildings, and a city wide network of workspaces, bars, cultural venues and other infrastructure. The squatted domain, as it developed at the time, can be viewed as an urban commons. For a section of the squatting community, the whole was far greater than merely the sum of its parts, which led to the creation of a horizontal, city level organization. Commoning strategies applied at the city level were organizing squatting days, setting up a collective process for legalization, and promoting alternative urban development. However, evictions prompted confrontational action and a number of groups adopted a confrontational identity. Operating outside the city-level organization, autonomous action teams formed. They perfected the skills involved in the defense of squats, and had informal leaders. Nevertheless, groups with both prefigurative and confrontational collective identities worked together, despite the cooperation being tenuous. The upshot was that a large number of squatter collectives were never evicted, but that squats were legalized instead.